Ensuring the security of personal data on the Internet: the commercial use of personal data by digital content providers - Stakhyra, Hanna; Savanets, Lyudmila (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article analyzes the legal aspect of the use of personal data by users of social online platforms. A comparative study of the concept of personal data protection in national and foreign legislation. Development of the Ukraine economy lead to creation new information society, digitization goods and services, rising level of person rights protection. With the framework of Association Agreement of the Ukraine and European Union it should harmonized legislation, and build wide common digital single market. Significant progress in the development of information technology, their widespread introduction, associated with the increase in volumes and areas of information use has led to the possibility of collecting, storing and processing information about the individual who is the subject of private law relations. In turn, due to the widespread use of automated systems and related technologies, information about any person may become one way or another open and lead to a violation of its lawful interests, material or non-pecuniary damage. But technology progress gives an opportunity to use personal data as a counter performance for getting goods and services in digital form. The emergence of such legal relations needs development and adoption some legislative regulation, which create maximum level of consumer rights protection. The concept of a contract for the supply of digital content is considered, according to which the user in exchange for digital content transmits to the online platform their personal data that can be used for marketing and advertising purposes. The provisions on the responsibility of the social online platform for the collection and transmission of data about its users to other persons, including for the implementation of political, marketing, social, economic, technological strategies, are analyzed.